2023
DOI: 10.1159/000529835
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors Underlying Parallel Changes in Body Mass Index and Alcohol Consumption: A 36-Year Longitudinal Study of Adult Twins

Abstract: Introduction: While the genetic and environmental underpinnings of body weight and alcohol use are fairly well-known, determinants of simultaneous changes in these traits are still poorly known. We sought to quantify the environmental and genetic components underlying parallel changes in weight and alcohol consumption, and to investigate potential covariation between them. Methods: The analysis comprised 4461 adult participants (58% women) from the Finnish Twin Cohort with four measures of alcohol consumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…Heritability estimates of BMI trajectories in FinnTwin12 adolescents (h 2 =63%) were slightly larger than those observed in adult Finnish twins (h 2 = 52-57%) [78], which is consistent with the higher heritability of BMI reported in younger populations [6] and further motivates the study of factors genetically associated with BMI changes during adolescence. Of body mass, fat accounts for a smaller proportion in children and adolescents in general, while gaining fat is more typical in adult populations The previous estimates for the heritability of plasma protein abundance associated with BMI trajectories appear to be rare in the literature.…”
Section: Discussionsupporting
confidence: 76%
“…Heritability estimates of BMI trajectories in FinnTwin12 adolescents (h 2 =63%) were slightly larger than those observed in adult Finnish twins (h 2 = 52-57%) [78], which is consistent with the higher heritability of BMI reported in younger populations [6] and further motivates the study of factors genetically associated with BMI changes during adolescence. Of body mass, fat accounts for a smaller proportion in children and adolescents in general, while gaining fat is more typical in adult populations The previous estimates for the heritability of plasma protein abundance associated with BMI trajectories appear to be rare in the literature.…”
Section: Discussionsupporting
confidence: 76%
“…Heritability estimates of BMI trajectories in FinnTwin12 adolescents (h 2 = 63%) were slightly larger than those observed in adult Finnish twins (h 2 = 52-57%) [85], which is consistent with the higher heritability of BMI reported in younger populations [6] and further motivates the study of factors genetically associated with BMI changes during adolescence. Of body mass, fat accounts for a smaller proportion in children and adolescents in general, while gaining fat is more typical in adult populations.…”
Section: Discussionsupporting
confidence: 76%
“…A prior meta-analysis of twin and adoption studies suggests that approximately 50% of the variation in alcohol use disorder (AUD) is explained by genetic factors, and 10% is attributable to environmental factors that are shared by co-twins (e.g., family income, parental divorce, neighborhood characteristics) (Verhulst et al, 2015). Recent longitudinal studies have further demonstrated that changes in frequency and quantity of alcohol use across adolescence and adulthood are influenced by genetic factors (Drouard et al, 2023;Zellers et al, 2022). However, genetic and environmental components of alcohol misuse trajectories from adolescence through early midlife have not been studied.…”
Section: The Current Studymentioning
confidence: 99%